Factors Affecting Farmer’s Decision to Use Loan at Rice-Fish Farming in Seyegan District, Sleman Regency, Yogyakarta - Appas, Herdi; Masyhuri, Masyhuri; Jamhari, Jamhari (HABITAT, 2018)
Capital is one of the important aspects in the development of farming system because with large capital, it is expected that the farming will run more and provide welfare for farmers who do the farming. Capital can be obtained from external sources by using loan. This research aims to determine the factors that influence the decision of farmers to use loan at Rice-Fish farming in Seyegan District, Sleman Regency, Yogyakarta. In this research, data were collected from 50 respondents by questionnaires and interviews with proportional sampling method where 25 respondents were taken from Margodadi Village, Seyegan District and adjusted to take 25 respondents from Margoluwih Village, Seyegan District. To analyze the factors that influence the decision of farmers using loan used Binary Logistic Regression Model. Partial test result shows that variables influence farmer's decision to borrow money are farmer’s education level, land area, the use of fish seeds, and loan procedures.